Integrasi Pranata Adat terhadap Sistem Demokrasi Lokal untuk Memperkuat Legitimasi Kepemimpinan Desa (Pusat Riset dan Inovasi Nasional, 2026)
The implementation of local democracy in Indonesia faces challenges when the electoral and procedural mechanisms regulated in modern village administration are not fully in line with the socio-cultural traditions of indigenous communities. Many villages still strongly uphold the values, norms, and authority of traditional institutions that have historically regulated communal life, including in terms of leadership legitimacy. Tension between formal democracy and customary values arises when the village political process is perceived as not reflecting the cultural identity of the community. This situation creates a need to understand how the integration of customary institutions can strengthen the legitimacy of village leaders in the local democratic system. This study uses a literature review method with a content analysis approach because the study focuses on the concept of the role of customary institutions in strengthening local democracy and the legitimacy of village leadership. This method allows researchers to explore theories and compare previous findings to form a systematic understanding. The research data comes from 19 secondary sources in the form of scientific books and journal articles published between 2016 and 2025 that are relevant to the themes of customs, village governance, community participation, and local leadership. The search was conducted using the Publish or Perish application with purposive sampling techniques to select sources directly related to the main research issue. This study concludes that the integration of traditional institutions into local democracy produces a model of village leadership that is legally strong and culturally rooted. This integration provides a basis for strengthening local democracy based on cultural wisdom, thereby supporting village development.